Clipping of Telomere from Human Chromosomes Using a Chemistry‐Based Artificial Restriction DNA Cutter. Issue 1 (2nd June 2015) - Ishizuka, Takumi; Xu, Yan; Komiyama, Makoto
Abstract: The detection of individual telomere lengths of human chromosomes can provide crucial information on genome stability, cancer, and telomere‐related diseases. However, current methods to measure telomere length entail shortcomings that have limited their use. Recently, we have developed a method for detection of individual telomere lengths (DITL) that uses a chemistry‐based DNA‐cutting approach. The most beneficial feature of the DITL approach is to cleave the sequence adjacent to the telomere followed by resolution of the telomere length at the nucleotide level of a single chromosome. In this unit, a protocol for successful detection of individual telomere lengths from individual chromosomes is described in detail. © 2015 by John Wiley & Sons, Inc.